Is cooperative green innovation better for carbon reduction? Evidence from China. (25th March 2023) - Zhao, Yuhuan; Zhao, Ziyi; Qian, Zhiling; Zheng, Lu; Fan, Shunan; Zuo, Sumin
Abstract: Alleviating global climate change requires the development and adoption of green innovation. This study compares the impact of cooperative and independent green innovation on carbon reduction based on the panel data covering 252 cities in China from 2003 to 2019. We examine the heterogeneous impacts of cooperative green innovation across units, and explain the transmission mechanism. The two-way fixed effects model and interaction model are adopted. Results show that: (1) Cooperative green innovation can reduce carbon emissions more effectively than independent green innovation. A 1% increase in cooperative green patents (inventions) will reduce carbon emissions by 0.023% (0.037%), while independent green patents or inventions play a weak role. (2) For research and development (R&D) partners, firms' cooperative green innovation has a stronger positive effect on carbon reduction than research organizations. The carbon reduction effect of cooperative green innovation is better for listed firms and universities. (3) Mechanism analysis shows cooperative green innovation can reduce carbon emissions by improving the industrial structure and decreasing energy intensity. These effects are stronger when cities have more talent, funds and higher marketability. (4) We also find that listed firms' cooperative green inventions with a ten-year lag can still reduce carbon emissions effectively. Cooperative green innovation is conducive to carbon reduction among eastern and central cities of China. Graphical abstract: Image 1 Highlights: This paper explores the impact of green innovation on carbon reduction from the new perspective of cooperation. Cooperative green innovation is more effective than independent green innovation in carbon reduction. Cooperative green innovation of listed firms and universities is more conducive to carbon reduction. Cooperative green innovation can optimize the industrial structure and decrease energy intensity for better carbon reduction. Cooperative green innovation with more talent, funds and market has better carbon reduction effect.